Kajian Hadis Nabi dalam Perspektif Pendidikan: (Kajian Materi Pembelajaran, Metode Pembelajaran, Hasil Pembelajaran dalam Hadis Sammillāh wa Kul Biyamīnika Riwayat ʿUmar bin Abī Salamah) - Maryono Maryono (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2020)
This study aims to discuss the Hadith of the Prophet ṣallallāh ʿalaih wasallam narrated by Umar bin Abi Salamah raḍiya Allāh 'anhū which intersects with the learning process from an educational perspective, namely materials, methods, learning outcomes. This research is included in the category of library research. The researcher records all the findings in general in each study discussion found in the literature and sources, collecting books in stages. The data is collected by documentation techniques, namely by reading (text reading), then reviewing, studying, and recording literature that is related to the focus of the study. The results of the study show that the educational material contained in the hadith history of Umar bin Abi Salamah raḍiya Allāh 'anhū includes Islamic adab-adab material, namely eating manners which includes reading bismillah before eating, eating with the right hand, eating the closest food. The learning method in the history of Umar bin Abi Salamah raḍiya Allāh 'anhū, the Prophet ṣallallāh ʿalaih wasallam, delivered material with the guidance method. While the learning outcomes are changes in attitudes and behavior as well as recognition from students, namely hadith narrators.